Sintesis dan Karakterisasi Komposit Hidroksiapatit/Kitosan/Alginat sebagai Injectable Bone Substitute (IBS) - RASMIYANTI; VINA AMALIA; SONI SETIADJI (Gunung Djati Conference Series, 2022)
Cases of osteoporosis to cause bone damage such as fractures require bone surgery through autograft, allograft and xenograft methods. Injectable Bone Substitute (IBS) is a bone filling material in the form of a suspension or paste. In the case of osteoporosis, the IBS method can be overcome because it can adjust to the bone cavity to be filled. One of the materials that can be made in the form of IBS is hydroxyapatite (HAp). HAp has similar properties to bone, but HAp is easily brittle, so it needs to be modified in the form of a composite by adding alginate and chitosan to increase its hardness. This study aims to investigate the properties of HAp/chitosan/alginate composites in the form of IBS through viscosity test, injectability test, setting time test, and pore size test. The method used to synthesize HAp was a sol-gel and HAp/chitosan/alginate composite using the ex-situ method with a mass ratio of HAp:chitosan:alginate (60:10:30), (60:20:20), and (60:30:10) through the process of mixing alginate solution and chitosan solution for 120 minutes. The viscosity value is related to the percentage of injectability, which is 35 dPa.s to 41 dPa.s at room temperature and the percentage of injectability is 91.05% to 97.57%. The setting time test in the HAp substrate was able to experience setting within 3 hours 11 minutes to 3 hours 58 minutes and experienced weight gain. The IBS suspension composition (60:20:20) was able to reduce the pore size as indicated by the SEM results from 5.76 m to 4.28 m.The viscosity value is related to the percentage of injectability, which is 35 dPa.s to 41 dPa.s at room temperature and the percentage of injectability is 91.05% to 97.57%. The setting time test in the HAp substrate was able to experience setting within 3 hours 11 minutes to 3 hours 58 minutes and experienced weight gain. The IBS suspension composition (60:20:20) was able to reduce the pore size as indicated by the SEM results from 5.76 m to 4.28 m.